Physiological and Structural Abnormalities of Coconut Plants (Cocos nucifera L.) at Different Stages of Growth and Plantation Sites under Low Temperature Condition in Bangladesh (The Agriculturists, 2016)
Physiological and structural changes of coconut plants at different growth stages and plantation sites under low temperature conditions was investigated during 1997-98, 2002-03, 2005-06 and 2009-10 in the northern region of Bangladesh. Three growth stages viz. < 7, 7-15 and > 15 years and three locations viz. road side, near pond and near drain were selected for this study. Leaf area damage with characteristics lesions categorized into mildly damaged, moderately damaged and dead plants. Age and planting site revealed very significant differences. The highest percent of dead (49.84-58.49 %), moderately damaged (37.20-46.21 %) and mildly damaged plants (65.70-74.79 %) were found in road side, while the highest percent of dead plants (39.93-45.58 %), moderately (20.18-26.68 %) and mildly damaged plants (69.46-70.37 %) were found in above 15 years old plants. The lowest percent dead of plants (20.82, 18.27 and 19.55 %) were found in pond side and (11.74, 12.53 and 13.31 %) in the 7-15 years old plants. The mean temperature, sunshine hours and total precipitations remained below 16.88 °C, 10.25 hours and 11.7 cm, respectively during 1997-98, 2002-03 and 2009-10. The highest amount of potassium (0.57 me/100 g soil) was found in pond side soil, whereas the lowest amount of potassium (0.11 me/100g soil) was found in road side soil. It has been concluded that low temperature (below 16.88 °C), mean precipitation 11.7 cm and amount of potassium 0.11me/100 g in soil were responsible for severe damage of the coconut plants in the study area.The Agriculturists 2015; 13(2) 113-119